Vivências do trabalho uberizado e saúde mental de entregadores de comida por aplicativos - Sousa, Ana Laís Carvalho de (2024)
Given the need to understand the psychosocial work environment, particularly within the context of the phenomenon of uberization, this study focuses on app-based food delivery workers. With the rise of globalization and Information and Communication Technologies (ICTs), the precariousness of labor relations today has contributed to the erosion of labor rights and the deterioration of workers’ physical and mental health. Thus, this study aims to understand how the experiences of uberized work are associated with the mental health of food delivery Workers in the city of Tianguá-CE. The study is grounded in the Psychodynamics of Work (PdW), a Work Clinic that seeks to focus on the worker’s subjectivity and understand the maintenance of a given psychological balance, even in contexts where working conditions are degrading. The theoretical categories of PdW used include: experiences of pleasure and suffering, defensive strategies, cooperation, practical intelligence, collective mobilization and recognition, in addition to health and illness processes. The research employed a qualitative and exploratory approach. Data were collected through individual, semi-structured interviews based on a guide developed from the research objectives. Participants were selected through convenience sampling using the snowball technique and saturation criterion. Data collection occurred after approval by the Research Ethics Committee. Data analysis was performed using core meaning analysis (CMA). The results indicated that the experiences of pleasure and suffering were conditioned by work contexto, including working day, weather conditions and interpersonal relationships. The defensive strategies identified included the use of caffeine, physical exercise, and time spent with family. It was observed that cooperation among delivery people occurs through communication via WhatsApp groups, where they help each other, facilitating work dynamics. Practical intelligence was perceived through cooperation among peers, which was even identified by their intention to jointly create their own application. It was also noted that there was a lack of collective mobilization. Furthermore, recognition was indicated to exist by some customers and establishments. In relation to health and illness processes, it was obserced that excessive working hours compromise health promotion, preventing delivery Workers from maintaining a regular routine for eating and sleeping. In addition, this situation makes them dependent on caffeine to sustain the alertness necessary for their exhausting routine. From the interviewees' perspective, mental health is generally understood as the well-being of the individual. However, work experiences and their psychodynamic processes, influenced by the work context, consistently compromise this well- being. The research highlighted specific demands for the development of public mental health policies targeting app-based delivery Workers. As a result of the research, the documentary “Invisible Price” is being developed as a potential technical product, aimed at bringing visibility to these workers. Furthermore, there is a need for new studies that cover other contexts of uberized work, as well as different regions, to broaden perspectives on the topic.